Job fair as a job recruitment tool - Anaya, Sheila Mae.; De Vicente, Joanna Mae.; Isonza, Karina Marie (2006.)
This study aims to investigate, identify and analyze job fair as a job recruitment tool, its activities, advantages, purpose and the problems encountered. Since the study is about job fairs in iloilo City, the researchers focused on the job fairs conducted in the past up to the recent ones only in Iloilo City.
Business Research (Mgt 199 - Business Research) -- [Iloilo City] : University of the Philippines in the Visayas - College of Management, October 13, 2006.